Frequency and Time Series Analysis of Surge Arrester in Power Distribution Systems - Alireza Zabihi; Mohammad Parhamfar (Advances in Engineering and Intelligence Systems)
Surge arresters are essential protective devices in power systems that redirect excess voltage and prevent damage to sensitive equipment. Extensive research has been conducted in electro-thermal modeling for surge arresters to better understand and mitigate faults and accidents. These efforts have largely focused on FEM and heat transfer modeling techniques to analyze temperature distribution, electric field effects, thermal-mechanical stress, burning point analysis, puncture risks, and thermal runaway behavior. This study also presents frequency and time series analysis of surge arresters during short circuits. By integrating these two analyses, engineers can enhance their understanding of surge arrester behavior during short circuits, refine design strategies to address issues like resonance and harmonics, and ensure reliable system protection against overvoltage occurrences.